Artificial Neural Network Modeling Of Hydrogen Uptake Based On Carbon Surface Area - Razak, N.A.; Arshad, K.A.; Rahman , A.A.; Ismail , A.F.; Sanip, S.M. (2004)
The discovery of carbon nanotubes (CNT) by Sumiio Iijima in 1991 has attracted many researchers worldwide to study and explore thc newly found materials. CNT are considered for hydrogen storage due to their low density, high strength, and hydrogen adsorption characteristics. Rcccnt reports suggest that total surfacc area of carbon affect the hydrogen storage capacities in carbon nanotubes. An Artificial Neural Network model was created to study the relationship between the surface area of carbon and the hydrogen adsorption.